Administrative and legal regulation of the limits for preventing and combating corruption in the public service - E. O. Muzychuk (Bulletin of Kharkiv National University of Internal Affairs)
The article states that the fight against corruption in the public service requires the regulatory and legal consolidation and organizational implementation of the limits for preventing corruption, by which we understand the actual definition of anti-corruption activities in laws and subordinate legal acts, as well as the existence at the organizational and institutional level of regulatory mechanisms the impact of social relations that arise in the course of the work of anti-corruption and law enforcement agencies in the field of preventing and countering corruption.